Orientasi Pengabdian Diri Orang Beriman Melalui Kajian Eksegesis Matius 6:19–24 - Natanael Apriyanto Tarigan (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2025)
This study examines the orientation of believers’ self devotion based on an exegetical analysis of Matthew 6:19–24. In the context of modern life characterized by materialism and consumerism, many believers experience a shift in their life orientation from God toward worldly concerns. This pericope emphasizes the impossibility of serving two masters and calls believers to store up treasures in heaven as an expression of genuine devotion to God. Therefore, this study aims to explore the theological meaning of Jesus’ teaching and its relevance for the lives of contemporary believers. The method employed is exegetical analysis using historical, grammatical, and theological approaches to the Greek text of the New Testament. The historical analysis seeks to understand the social and religious background of the first century, while the grammatical analysis focuses on key terms such as thēsauros (treasure), douleuein (to serve), and Mammon. The theological approach is then used to formulate the spiritual message of the text, highlighting the exclusive nature of devotion to God. The exegetical findings indicate that believers’ self devotion encompasses three main principles. First, a life orientation centered on earthly wealth has a negative impact on spiritual life, as it is transient and has the power to bind the heart. Second, devotion to God demands total and undivided commitment, thereby eliminating any compromise between God and Mammon. Third, genuine devotion is manifested through a life orientation focused on eternal values by storing up treasures in heaven. These findings affirm the continued relevance of Jesus’ teaching in Matthew 6:19–24 as a guide for believers in reorienting their lives to be centered on God.AbstrakPenelitian ini mengkaji orientasi pengabdian diri orang beriman berdasarkan eksegesis Matius 6:19–24. Dalam konteks kehidupan modern yang ditandai oleh materialisme dan konsumerisme, banyak orang percaya mengalami pergeseran orientasi hidup dari Allah kepada kepentingan duniawi. Perikop ini menegaskan ketidakmungkinan mengabdi kepada dua tuan serta mengarahkan orang beriman untuk mengumpulkan harta di surga sebagai wujud pengabdian sejati kepada Allah. Tujuan penelitian ini adalah menggali makna teologis pengajaran Yesus dan relevansinya bagi kehidupan orang beriman masa kini. Metode yang digunakan adalah eksegesis dengan pendekatan historis, gramatikal, dan teologis terhadap teks Yunani Perjanjian Baru. Analisis historis digunakan untuk memahami latar sosial dan religius abad pertama, sedangkan analisis gramatikal menyoroti istilah kunci seperti thēsauros (harta), douleuein (mengabdi), dan Mamon. Pendekatan teologis kemudian merumuskan pesan rohani yang menekankan eksklusivitas pengabdian kepada Allah. Hasil eksegesis menunjukkan bahwa pengabdian diri orang beriman mencakup tiga prinsip utama. Pertama, orientasi hidup yang berpusat pada harta duniawi berdampak negatif terhadap kehidupan rohani karena bersifat fana dan mengikat hati. Kedua, pengabdian kepada Allah menuntut komitmen total dan tidak terbagi, sehingga meniadakan kompromi antara Allah dan Mamon. Ketiga, pengabdian sejati diwujudkan melalui orientasi hidup pada nilai-nilai kekekalan dengan mengumpulkan harta di surga. Temuan ini menegaskan relevansi ajaran Yesus dalam Matius 6:19–24 sebagai pedoman bagi orang beriman untuk menata kembali orientasi hidupnya agar berpusat pada Allah.